ANALISIS KINERJA HOMESCHOOLING KAK SETO SOLO DENGAN MENGGUNAKAN PERSPEKTIF KEUANGAN DAN NON KEUANGAN - Untung Sriwidodo, Anna Widyati, Y. Djoko Suseno & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2017)
This research is conducted to know the financial perspective as aperformance measurement and to know significancy non-financialperspective are simultaneously significancy with performance; financialperspective, customer perspective, internal business process, learn andgrowth perspective are significancy with performance. This research issurvey research which is located at Homeschooling Kak Seto Solo. Thesample is 60 persons which are using sensus method to inquiry sheetthrough validity and reliability test. The analysis technique uses doubleregression with classical assumpttion. The analysis result shows financialperspective as a performance measurement and non-financial variable isaffect to the performance too. It takes from the hypothesis: financialperspective as a Homeschooling Kak Seto Solo’s performance measurementis true and non-financial perspective is significancy with Homeschooling KakSeto Solo’s performance is true.Keywords: performance, financial perspective, non-financial perspective,customer perspective, internal business process perspective,learning, growth perspective